Multi-Point Wireless Temperature Sensing System for Monitoring Pharmaceutical Lyophilization - Jiang, Xiaofan; Zhu, Tong; Kodama, Tatsuhiro; Raghunathan, Nithin; Alexeenko, Alina; Peroulis, Dimitrios (Frontiers in Chemistry, 2018)
This work presents the design and evaluation of a fully wireless, multi-point temperature sensor system as a Process Analytical Technology (PAT) for lyophilization. Each sensor contains seven sensing elements which measure the product temperature at various positions of the contents of a glass vial. The sensor performance was studied by freeze-drying experiments with sensor placement in both center and edge of full shelf of 6R glass vials with 4ml fill volume. Product temperature profile and primary drying time measured at the bottom center position in the glass vial by the wireless sensor as well as the primary drying time are in close comparison with the thermocouple data. The drying times during primary drying were determined at the top, higher middle, lower middle and bottom positions which are 3.26 mm apart vertically in the vial by the wireless sensor based on the temperature profile measured at different positions. For a center vial, the drying time from the start of primary drying to each layer was measured at 3.9, 9.3, 14.2 and 21 hours respectively, allowing to track the sublimation interface during primary drying phase. In addition, sublimation rate at each layer was calculated based on the drying time and theoretical weight loss of ice in the product. The sublimation rate at the beginning of the primary drying was similar to the sublimation rate by gravimetric method. Furthermore, the vial heat transfer coefficient (Kv) was also calculated based on the sublimation rate. Thus allowing the use of the multi-point wireless sensor to rapidly monitor the sublimation rate and Kv for every batch as continuous process verification. Similar tests were also conducted with 3% w/v mannitol solutions and the results were consistent demonstrating potential for real-time monitoring, process verification and cycle optimization for pharmaceutical lyophilization.